Financial Management and Profitability in a Private Company in the Construction Sector of the District of San Borja – 2022 - Junior, Escalante Huamán, Robert; Ronald, Machaca Yana; Jesús, Alcantara Molina, Carlos (Migration Letters, 2024)
The current study was carried out in a company in the construction sector focused on short and medium-term projects, with the objective of establishing the relationship between financial management and profitability, in order to determine whether applying an improvement in the first of these has a significant influence on the second. The method used was a non-experimental method of basic quantitative correlational scope, using as a sample 27 workers from four different areas of the organization, by means of a questionnaire that describes both variables. The reliability obtained was 0.928 and 0.863 according to Cronbach. Once applied, it was determined that, according to Spearman’s correlation coefficient, this relationship is significant and with a value of 0.819, therefore, it was concluded that a better management of financial management as a useful tool for decision-making, could improve the profitability of the company under study.